Judicial Transformation and Institutional Independence in Early Islam: Evidence from The Rightly Guided Caliphs - Ilfah Luthfiah; Supardin; Muh. Rusdi T (Jurnal Kajian Islam Interdisipliner, 2026)
This study aims to analyze the transformation of the Islamic judicial system during the era of the Rightly Guided Caliphs. This research is grounded in the urgency of understanding the development of the Islamic legal system following the passing of the Prophet Muhammad (peace be upon him), where the complexity of social challenges spurred the emergence of fresh dynamics in judicial institutions. The primary focus is on the transformation of the judicial system, which shifted from the singular authority of Prophet Muhammad (peace be upon him) to a more structured framework during the era of the Khulafa al-Rashidin (Rightly Guided Caliphs). This study is positioned as a comparative-historical analysis, using that classical period as a foundation for advancing contemporary Islamic judicial management. The applied approach employs descriptive qualitative methods through library research, supplemented by content analysis of primary and secondary sources. The findings reveal that the judicial patterns during Abu Bakr's time retained the simplicity of the prophetic era, but underwent a striking transformation under Umar bin Khattab, marked by the separation of judicial functions from the executive and the appointment of independent judges (qadhi). This development continued under Uthman and Ali through the reinforcement of procedural justice principles and the integrity of judges. Overall, the era of the Khulafa al-Rashidin laid the foundation for the supremacy of law, consultative mechanisms (shura), and the independence of judicial institutions, which remain relevant to this day. These findings contribute to contemporary debates on Islamic legal governance by demonstrating that judicial independence has deep historical roots in early Islamic political structures.